Who Shapes the Land: Actor-Centered Perspectives on Western Canadian Settlement (1881-1918) - McIntyre, Marice (Peer Beyond Graduate Research Conference, 2025)
This paper proposes a theoretical and methodological model to reinterpret Western Canadian settlement in Alberta and Saskatchewan (1881–1918) using an actor-centered approach that integrates Actor-Network Theory and Structuration Theory. Combining quantitative and qualitative methodologies from History, Geoscience, Sociology, and Indigenous studies.